Antagonistic yeasts for the biological control of Penicillium digitatum on lemons stored under export conditions - Perez, Maria Florencia (2017)
The main phytopathogen that affects lemons in the postharvest stage is Penicillium digitatum. Currently, chemical fungicides which have been shown to have negative impacts on both, the environment and human health are used to combat fungus decay. As alternatives to the use of these fungicides killer yeasts which were previously isolated from citrus plants, showed an effective biocontrol effect against Penicillium spp. In order to determine the efficacy of selected killer yeasts throughout the harvest period, in vivo protection trials were performed at both room and low temperature; these trials were carried out under similar conditions to those applied for export to overseas markets. In addition, tolerance to commonly used postharvest fungicides was also tested. Clavispora lusitaniae 146 and Pichia fermentans 27 showed high and consistent protection during the whole harvest period in both temperature conditions. Even their protection efficiencies were superior to a commercial product based on Candida oleophila. Strains 146 and 27 were tolerant to fungicides; therefore; combined application of chemical agents along with the biocontrol agent could be employed in postharvest stages.